(3EbJUGOjGJ GdScGf hGdehGQO GdHTQjI (B:s (3EWGQ fXQj hJWHjbj (B/s - (3YHO GdQGRb, eMehO MGeOs ((3MdhGf(B: s (3ecJHI GdMQjI ddfTQ h GdJhRjY(B, s)
(3ehbY GdGbJUGO GdScGfj aj GdOQGSGJ GdGbJUGOjI, eaghe hCgejI hfWGb GdGbJUGO GdScGfj, GdGWGQ GdfXQj ddXGgQI GdScGfjI, GdScGf hGdJfejI GdGbJUGOjI, JLGQH GdOhd aj hVY GdSjGSI GdScGfjI, GdgLQI GdOhdjI ddScGf, GfJGLjI Gdbhi GdYGedI hGdScGf hShb GdYed, GdeaGgje GdCSGSjI ddScGf heYOd Gdfeh GdScGfj, GdScGf hGdJfejI GdHTQjI aj eUQ, GdJYdje hGfYcGSGJg GdScGfjI, GdHWGdI hGdScGf aj GdOhd GdfGejI, GdScGf Hjf GdQja hGdMVQ, GdHWGdI hGdScGf aj eUQ, Gdfeh GdScGfj aj GaQjbjG, GdgLQI GdOhdjI hGdeMdjI hGdGbdjejI ddScGf aj GaQjbjG, GdScGf hGdJfejI GdHTQjI aj GdfXGe GdGbJUGOj GdGSdGej(B.s
(3HjHdjhZQGajG(B: (3U(B.249s
Keywords: (3GdJfejI GdGbJUGOjIs; (3GdScGfs; (3Gdbhi GdYGedIs